2021
DOI: 10.3390/su13105402
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Prediction of PM10 and PM2.5 from Road Source Emissions in Kuala Lumpur City Centre

Abstract: Particulate matter (PM) is one of the major pollutants emitted by vehicles that adversely affect human health and the environment. This study evaluates and predicts concentrations and dispersion patterns of PM10 and PM2.5 in Kuala Lumpur city centre. The OML-Highway model calculates hourly time series of PM10 and PM2.5 concentrations and distribution caused by traffic emissions under different scenarios; business as usual (BAU) and 30% traffic reduction to see the impact of traffic reduction for sustainable tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…Particulate matter (PM) is considered one of the most harmful components of ambient pollutants to humans [ 3 ]. Recent studies in the city of Kuala Lumpur, Malaysia demonstrated that PM pollution in this area is greatly contributed by vehicle emissions [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter (PM) is considered one of the most harmful components of ambient pollutants to humans [ 3 ]. Recent studies in the city of Kuala Lumpur, Malaysia demonstrated that PM pollution in this area is greatly contributed by vehicle emissions [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study utilizes hourly historical air quality dataset which consisting of six air pollutant parameters namely particulate matter (PM2.5 and PM10), sulphur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), ozone (O 3 ) and carbon monoxide (CO) from two air quality monitoring stations located in Kuala Lumpur, Malaysia. Kuala Lumpur is Malaysia's capital city, the country's most developed and densely populated city 26 . The reason for selecting such datasets is because Kuala Lumpur the capital city of Malaysia with the highest rate of industrial activities, urbanization and traffic congestion.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental aspects provide a significant role in increasing the global incidence of respiratory diseases perceived in recent decades [ 61 , 62 ]. In particular, asthma and nasal conjunctivitis mostly contribute to the global issue of diseases, with a world urban health incidence of schoolchildren of 5–20% and 0.8–39.7%, respectively [ 63 , 64 ].…”
Section: Literature Reviewsmentioning
confidence: 99%